Exosomes as a biomarker platform for detecting epidermal growth factor receptor-positive high-grade gliomas - Manda, Sasidhar Venkata; Kataria, Yogesh; Tatireddy, Babul Reddy; Ramakrishnan, Balasubramaniam; Ratnam, Boola Gnana; Lath, Rahul; Ranjan, Alok; Ray, Amitava (Journal of neurosurgery, 2018)
OBJECTIVE High-grade glial brain tumors are often characterized by an elevated expression of the tumorigenic epidermal growth factor receptor variant III ( EGFRvIII). The authors sought to establish a clinically adaptive protocol as a noninvasive diagnostic tool for EGFRvIII detection through serum exosomes. METHODS Purity of serum exosome/RNA was confirmed by electron microscopy and flow cytometry and through an RNA bioanalyzer profile. EGFRvIII amplification was initially established by semiquantitative polymerase chain reaction in tumor tissues and exosomes. Diagnostic performance of EGFRvIII transcript in tissue versus exosome was determined using a 2 × 2 clinical table approach. Overall survival was determined using Kaplan-Meier analysis. RESULTS The EGFRvIII transcript was detected in 39.5% of tumor tissue samples and in 44.7% of their paired serum exosome samples; 28.1% of biopsy tumors coexpressed wild-type EGFR and EGFRvIII. Tissue EGFRvIII amplification served as the reference-positive control for its paired serum expression. The overall clinical sensitivity and specificity of semiquantitative exosome EGFRvIII polymerase chain reaction detection assay in serum were 81.58% (95% CI 65.67%-92.26%) and 79.31% (95% CI 66.65%-88.83%), respectively. Age, sex, tumor location, and side of the body on which the tumor was located had no effect on the detection rate of exosomal EGFRvIII transcript. EGFRvIII expression either in exosomes or tissue correlated with poor survival. CONCLUSIONS The authors established a serum-based method for detection of EGFRvIII in high-grade brain tumors that might serve as an optimal noninvasive method for diagnosing EGFRvIII-positive high-grade gliomas.